Fatigue Pictogram: an option for assessing fatigue severity and impact - Mota, Dálete Delalibera Corrêa de Faria; Pimenta, Cibele Andrucioli de Mattos; Fitch, Margaret Isabel (Revista da Escola de Enfermagem da USP, 2009)
The purpose of this paper was to validate the Fatigue Pictogram for use in Brazil. Data was collected at four oncology ambulatory clinics in Sao Paulo (Brazil) and at the Nursing School of Sao Paulo University. A convenience sample of 584 cancer patients, 184 caregivers and 189 undergraduate nursing students completed the Karnofsky Scale, Fatigue Pictogram-Brazilian Version, and the Beck Depression Inventory (BDI). Validity and reliability tests were performed. Test-retest showed that the instrument has good stability. The first item of the Fatigue Pictogram discriminated students from caregivers and patients but not patients from caregivers. The second item discriminated among all groups. Adequate convergent (fatigue and depression) and divergent (fatigue and Karnofsky Scale) validity was observed. The Fatigue Pictogram is a valid, reliable, and easy-to-use tool for assessment of cancer-related fatigue but needs adjustments for use among healthy individuals.